RESEARCH MAPPING OF BLUE CARBON AND MANGROVE PLANTS IN INDONESIA : BIBLIOMETRIC ANALYSIS WITH SCOPUS DATABASE 2014-2024 - Winoto, Yunus; Rodiah, Saleha; Prijana, Prijana; NurIslaminingsih, Rizki; Diana Saiful Bahry, Farrah; Ijlal Septian, Falih (Jurnal Belantara, 2025)
Indonesia is one of the countries with the largest blue carbon ecosystems in the world. This is due to its long coastline and vast marine areas. Indonesia has the largest mangrove forests in the world, covering approximately 3.3 million hectares, spread across the coasts of Sumatra, Kalimantan, Sulawesi, Papua, and Java. The method used in this research is bibliometric analysis, a quantitative approach to analyzing scientific literature to identify publication patterns, research trends, scientific impact, author collaborations, and relationships between scholarly works. Based on the results, it was found that among the 10 most productive authors, Murdiyanto is the most productive, with 13 publications. In terms of institutional affiliation, authors come from institutions such as Bogor Agricultural University, the National Research Agency, and the Center for International Forestry Research. Bibliometric mapping using Vos-viewer, through co-occurrence analysis for network, overlay, and density visualization, shows that topics related to blue carbon and mangroves, such as organic carbon, carbon storage, carbon emissions, and mangroves, were trending between 2021 and 2024. However, these topics as a whole have not been widely researched.